A year-long assessment of wave measurements retrieved from an HF radar network in the Gulf of Naples (Tyrrhenian Sea, Western Mediterranean Sea). Issue 1 (2nd January 2019) - Saviano, Simona; Kalampokis, Alkiviadis; Zambianchi, Enrico; Uttieri, Marco
ABSTRACT: A three-site short-range (25 MHz) CODAR SeaSonde High-Frequency (HF) radar system has been operating in the Gulf of Naples (Tyrrhenian Sea) since 2004. HF radars use first-order echoes to determine surface currents, while second-order ones can be exploited to estimate the main parameters characterising the wave field: significant wave height, direction and period. Waves were studied in the Gulf of Naples at each radar site over a range cell located between 5 and 6 km from the coast. The data acquired in the reference year 2010 were compared with the measurements recorded over the same period by a directional wave buoy installed in the outer part of the basin. This study aims at verifying the agreement between the recordings of the two platforms, in order to test the robustness of the HF radar-derived wave measurements. In addition, the analyses here presented investigate the seasonal patterns of the wave parameters, showing the different responses of the wave field in different sectors of the basin and the responsiveness of HF radars in critical environmental conditions. The two platforms showed consistent results, indicating the reliability of HF radars as wave measurement tools and opening the way to further applications in wave monitoring and analysis in coastal areas.